Adsorption of mercury contaminated synthetic water by fly ash from coal fired power plant - Kitchainukul, Waraporn (Bulletin of Applied Sciences, 2013)
Fly ash from the coal fired power plant can be applied to many methods of solid waste disposal such as solidification, used as combined material in constriction industries and etc. The adsorption equilibrium was reached after 96 hours. The adsorption capacity of the fly ash for Hg (II) was found to be 3.5 mg g-1 of dry ash. The absorption isotherms with pH from 7.0 to 8.0 and used 10 g of fly ash per 1 l of initial Hg concentration were the optimize condition. The leaching test of mercury bond fly ash is lower than legal concentration (less than 2 mg/l). The results indicated that fly ash from coal fired power plant can be used to stabilize low concentration of mercury in aquatic condition.